Development of generic core competences of health professionals in rheumatology: a systematic literature review informing the 2019 EULAR recommendations. Issue 2 (23rd October 2019) - Fragoulis, George E; Edelaar, Lisa; Vliet Vlieland, Theodora P M; Iagnocco, Annamaria; Schäfer, Valentin Sebastian; Haines, Catherine; Schoones, Jan; Nikiphorou, Elena
Abstract : Objective: To identify generic competences on the desired knowledge, skills and of health professionals in rheumatology (HPRs) to inform the respective EULAR recommendations. Methods: A systematic literature review was performed on the generic core competences (defined as knowledge, skills or attitudes) of HPRs (nurses, physical therapists (PTs) or occupational therapists (OTs)). Literature was obtained from electronic databases, published EULAR recommendations and via personal communication with representatives of national rheumatology societies and experts in the field. Qualitative, quantitative and mixed methods studies were included, and their methodological quality was scored using appropriate instruments. Results: From 766 references reviewed, 79 fulfilled the inclusion criteria. Twenty studies addressed competences of multiple HPRs: 15 were of qualitative design, 1 quantitative, 1 mixed-methods, 2 systematic reviews and 1 opinion paper. The methodological quality of most studies was medium to high. Five studies concerned the development of a comprehensive set of competences. Key competences included: basic knowledge of rheumatic diseases, holistic approach to patient management, effective communication with colleagues and patients and provision of education to patients. The proposed competences were confirmed in studies focusing on one or more specific competences, on a rheumatic disease or on a specific profession (nurses, PTs or OTs). Conclusion: Generic competences were identified for HPRs. Data were mostly derived from qualitative studies. All identified studies varied and were at national level, highlighting the need for the harmonisation of HPR competences across Europe. These findings underpin the development of EULAR recommendations for the core competences of HPRs.